HUBUNGAN KECERDASAN INTELEKTUAL TERHADAP KETERAMPILAN BERMAIN SEPAKBOLA AKADEMIK JONG ACEH - Syahasti, Frisha; Musran, Musran; Kurniawan, Erizal; Syahrinursaifi, Syahrinursaifi; Yulinar, Yulinar (Center for Research and Community Service (LPPM) University of Abulyatama, 2024)
The game of football besides demanding physical conditions, intellectual intelligence also plays a role to make it easier for players in mastering football skills and be able to play well. The purpose of this study is to determine the correlation between Intellectual Intelligence and Jong Aceh Academic football playing skills. This study approach used quantitative with a correlational type. The population and sample for this study were 18 Jong Aceh Academic players. This research data collection also consisted of two test items, there are Intelligence quotes and football playing skills. The results of this study showed that the SPSS output Pearson Correlation X.Y, = 0.644 ≥ F Table = 0.468, it mean the intellectual intelligence have a meaningful relation to the football skills, and affected 41,47%. then the output Sig results. (2-tailed) = 0.004 ≤ 0.05. It can be concluded that there is a significant and positive correlation between intellectual intelligence and soccer playing skills at the Jong Aceh Academy